The palisade cartilage tympanoplasty technique: a systematic review and meta-analysis - Caroline C. Jeffery; Cameron Shillington; Colin Andrews; Allan Ho (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Tympanoplasty is a common procedure performed by Otolaryngologists. Many types of autologous grafts have been used with variations of techniques with varying results. This is the first systematic review of the literature and meta-analysis with the aim to evaluate the effectiveness of one of the techniques which is gaining popularity, the palisade cartilage tympanoplasty. PubMed, EMBASE, and Cochrane databases were searched for "palisade", “cartilage”, “tympanoplasty”, "perforation" and their synonyms. Main body of abstract In total, 199 articles reporting results of palisade cartilage tympanoplasty were identified. Five articles satisfied the following inclusion criteria: adult patients, minimum 6 months follow-up, hearing and surgical outcomes reported. Studies with patients undergoing combined mastoidectomy, ossicular chain reconstruction, and/or other middle ear surgery were excluded. Perforation closure, rate of complications, and post-operative pure-tone average change were extracted for pooled analysis. Study failure and complication proportions that were used to generate odds ratios were pooled. Fixed effects and random effects weightings were generated. The resulting pooled odds ratios are reported. Palisade cartilage tympanoplasty has an overall take rate of 96% at beyond 6 months and has similar odds of complications compared to temporalis fascia (OR 0.89, 95% CI 0.62, 1.30). The air-bone gap closure is statistically similar to reported results from temporalis fascia tympanoplasty. Conclusions Cartilage palisade tympanoplasty offers excellent graft take rates and good postoperative hearing outcomes for perforations of various sizes and for both primary and revision cases. This technique has predictable, long-term results with low complication rates, similar to temporalis fascia tympanoplasty.